Qualidade fisiológica e sanitária de sementes de Carthamus tinctorius L. (asteraceae) submetidas à termoterapia e ao armazenamento e produção de hastes florais e sua conservação em pós-colheita - Menegaes, Janine Farias (2019)
Carthamus tinctorius L. (safflower), belonging to the family Asteraceae and originating in Asia, is an annual and rustic plant with multiple purposes for use from culinary, pharmaceutical, oleiferous to ornamental. Thus, the objective of this work was to evaluate the physiological and sanitary quality of safflower seeds submitted to thermotherapy and storage, and the production of floral stems and their post-harvest conservation. In the period from 2016 to 2018, several experiments were conducted that are presented in this work in the form of six chapters. The experiments were carried out in the Didactic and Seed Research Laboratory, in the Biometry Laboratory and in the Floriculture Sector of the Phytotechnology Department, ranging from the adequacy of treatments to seed storage and the cultivation and post-harvesting of floral stems. In Chapters I and II the physiological and sanitary quality of the seeds was evaluated by the suitability of the thermotherapy methodology through wet and dry heat, respectively, as seed treatment. It was observed that the treatments of 45º C 15 min-1 and 45º C 24 h-1 were efficient in the reduction of the pathogens on the seeds, propitiating improvement in the germinative potential and in the emergency in the field. In Chapter III the physiological and sanitary quality of the seeds submitted to different treatments of thermotherapeutic seeds, chemical, biological and vegetal extracts were evaluated. It was verified that all the treatments promoted an increase in the germination and the emergence in the field, at the same time, that these were efficient in the control of the infestation of the pathogens on the seeds. In chapter IV the storage of seeds treated by thermotherapy was evaluated for 12 months. It was observed that the quality of these seeds was not maintained, presenting a decline in the percentages of germination and emergence in the field, from four months of storage. Chapter V evaluated the cultivation of flower stems treated by thermotherapy and sown at different times. It was verified that the treatments of seeds by thermotherapy were beneficial for the initial establishment of the seedlings in the field. And, that the development and the duration of the cycle of cultivation of the floral stems were different for all the times of sowing, with maintenance of the ornamental characteristics and the quality of the floral stems. Chapter VI evaluated the post-harvest quality and durability of fresh flower stems harvested at different times and submitted to different preservative solutions. It was observed that the floral stems had vessel life in average of nine days and that the use of the preservatives was not beneficial to the post-harvest conservation. In general, it is concluded that the adequacy of the methodology of thermotherapeutic treatments via wet and dry heat, confirms an alternative for the treatment of seeds, allowing an adequate initial establishment of the plant stand. With the feasibility of cultivating flower stems in all seasons of the year, with typical ornamental characteristics, average durability of nine days according to the conservation form.